Synthesis and fluorescence property of 2, 3-naphthalimide derivatives bearing phenyl substituents on the naphthalene skeleton. (January 2017) - Yanagisawa, Tatsuya; Kobayashi, Naoki; Shimosasa, Haruki; Kumai, Yoshimitsu; Miyatake, Ryuta; Oda, Mitsunori
Abstract: New 2, 3-naphthalimide derivatives bearing phenyl substituents on the naphthalene skeleton were synthesized, and their UV/vis absorption and fluorescence properties were investigated. The fluorescence intensity of the short wavelength emission was strengthened as the increase in the number of the phenyl groups on the naphthalene skeleton. Graphical abstract: Highlights: 2, 3-Naphthalimides bearing phenyl groups on the naphthalene moiety have been synthesized. The emission of the short wavelength was strengthened by introduction of phenyl groups. Fluorescence behaviors of N -aryl-2, 3-naphthalimides were demonstrated by theoretical calculations.